2023
DOI: 10.1002/smll.202206936
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Blocking the Calcium Overload/ROS Production Feedback Loop to Alleviate Acute Kidney Injury via Microenvironment‐Responsive BAPTA‐AM/BAC Co‐Delivery Nanosystem

Abstract: AKI is a common clinical syndrome with manifestations of progressive decrease in glomerular filtration rate to less than 75%, an abnormal increase in creatinine (CRE) and blood urea nitrogen (BUN), and a urine output of less than 0.5 mL kg −1 h −1 . [2] Continued deterioration of renal function to the point of toxin accumulation, dehydration/electrolyte disturbance, and acid-base imbalance can result in acute renal failure with a hospital mortality rate of 50% or more if not treated promptly and thoroughly. [3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Endothelial dysfunction induced by this endothelial damage in turn aggravates the reduction of organ blood flow during I/R through inflammatory response and changing vascular tone . Previous reports suggested that ameliorating calcium overload and microvascular endothelial dysfunction will lessen I/R-generated renal damage. , The regulatory relationships of CAD on calcium overload and endothelial dysfunction are rarely reported, which also motivates us to figure out their relationship in future studies. The established studies validated CAD’s biomedical properties in diversified disorders including ovarian cancer, cardiotoxicity, colon tumorigenesis, breast cancer, etc. , We originally figured out that CAD application could prevent the progression and end point of UUO or renal I/R surgery through anti-inflammatory and antioxidative authorities.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Endothelial dysfunction induced by this endothelial damage in turn aggravates the reduction of organ blood flow during I/R through inflammatory response and changing vascular tone . Previous reports suggested that ameliorating calcium overload and microvascular endothelial dysfunction will lessen I/R-generated renal damage. , The regulatory relationships of CAD on calcium overload and endothelial dysfunction are rarely reported, which also motivates us to figure out their relationship in future studies. The established studies validated CAD’s biomedical properties in diversified disorders including ovarian cancer, cardiotoxicity, colon tumorigenesis, breast cancer, etc. , We originally figured out that CAD application could prevent the progression and end point of UUO or renal I/R surgery through anti-inflammatory and antioxidative authorities.…”
Section: Discussionmentioning
confidence: 98%
“…54 Previous reports suggested that ameliorating calcium overload and microvascular endothelial dysfunction will lessen I/Rgenerated renal damage. 53,54 The regulatory relationships of CAD on calcium overload and endothelial dysfunction are rarely reported, which also motivates us to figure out their relationship in future studies. The established studies validated CAD's biomedical properties in diversified disorders including ovarian cancer, cardiotoxicity, colon tumorigenesis, breast cancer, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several passive targeting approaches were used, including: (1) small NPs (,10 nm) which pass through the glomerular filtration barrier and are reabsorbed in the nephron, (2) somewhat larger NPs which pass through the glomerular endothelial fenestrations and arrest in the glomerular mesangium (typically up to 80 nm), (3) somewhat larger (approximately 100 nm) NPs which pass through only disrupted glomerular filtration barriers and are reabsorbed in the nephron, and (4) NPs which do not interact with the glomerulus and cross from the peritubular endothelium into the tubular epithelium. Active targeting of NPs to the kidneys has taken several different approaches, including serine modifications which purportedly bind kidney injury molecule-1, 64,71,83,93 charge-based binding to the megalin receptor, 55,59,60,75 or other cell surface receptor or basement membrane binding. 51,68,70,85 Regarding therapeutic cargoes, we found that many of the active pharmaceutical ingredients (APIs) involved short interfering RNA (siRNA) delivery-about 10 of those we found.…”
Section: Glomerular Mesangium Targeting In Healthy Ratsmentioning
confidence: 99%
“…Meanwhile, a stabilized nanocarrier must undergo a structural change for efficient intracellular destabilization induced by one or more external/internal triggers to exert the desired therapeutic efficiency. , In this regard, the leading strategies adopted to induce the destabilization of a cyclic polymer-based nanocarrier mainly focused on the modification and functionalization of the side chains of cyclic polymers. Notable examples were cyclic polymers constructed with either stimuli-responsive monomers or intracellular triggers-cleavable links, which, however, inevitably led to inadequate intracellular drug release due to the lack of cyclic topology disruption . A stimuli-responsive cyclic backbone is thus highly desirable for promoted intracellular drug release but remains relatively unexplored likely due to the synthetic challenge.…”
mentioning
confidence: 99%